ANALISIS KADAR SAPONIN PADA EKSTRAK DAUN KELOR (Moringa oleifera Lam.) SECARA GRAVIMETRI - Nurkhasanah, Tika Aprilia; Dhurhania, Crescentiana Emy (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Moringa leaves (Moringa oleifera Lam.) have antimicrobial activity. One of the compounds that play a role in this activity is saponins. The purpose of this study was to determine the levels of saponins present in Moringa oleifera Lam. leaf extract by gravimetric method. Moringa leaves are extracted by maceration. The existence of saponins in Moringa oleifera Lam. leaf extract was proven through qualitative tests using foam tests and color tests, while analysis of saponin levels in quantitative tests was carried out using the gravimetric method with the principle of preparation. The results of the qualitative test showed that the Moringa oleifera Lam. leaf extract was positive for saponins. Analysis of saponin content was carried out gravimetrically with the principle of precipitation. The results of saponin analysis in Moringa leaf extract obtained results with an average of 3.959% with a coefficient of variation of 0.0420%.